Disruption of plastid acyl:acyl carrier protein synthetases increases medium chain fatty acid accumulation in seeds of transgenic Arabidopsis. Issue 7 (20th February 2013) - Tjellström, Henrik; Strawsine, Merissa; Silva, Jillian; Cahoon, Edgar B.; Ohlrogge, John B.
Abstract : Engineering transgenic plants that accumulate high levels of medium‐chain fatty acids (MCFA) has been least successful for shorter chain lengths (e.g., C8). We demonstrate that one limitation is the activity of acyl‐ACP synthetase (AAE) that re‐activates fatty acids released by acyl‐ACP thioesterases. Seed expression of Cuphea pulcherrima FATB acyl‐ACP thioesterase in a double mutant lacking AAE15/16 increased 8:0 accumulation almost 2‐fold compared to expression in wild type. These results also provide an in planta demonstration that AAE enzymes participate not only in activation of exogenously added MCFA but also in activation of MCFA synthesized in plastids. Abstract : ► Acyl‐ACP synthetase (AAE) activates fatty acids (FA) synthesized in planta . ► AAE suppression is a novel method to increase medium chain FA in transgenic seeds. ► 8:0 levels in seeds were approximately doubled in aae lines.